2017
DOI: 10.1089/met.2016.0132
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Epicardial Fat and Nonalcoholic Fatty Liver Disease on Heart Rate Recovery in Metabolic Syndrome

Abstract: EFT and NAFLD were significantly correlated with HRR in patients with MetS and they may be highly related to increased cardiovascular risk. These results suggest a cross-link among EFT, NAFLD, and cardiac autonomic dysfunction in patients with MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A total of 58 articles were excluded because they did not meet the inclusion criteria. Finally, 18 articles (thirteen cross-sectional studies (Fracanzani et al, 2016[ 7 ]; Brouha et al, 2018[ 3 ]; Cho et al, 2017[ 4 ]; Kim et al, 2016[ 18 ]; Psychari et al, 2016[ 33 ]; Petta et al, 2015[ 32 ]; Granér et al, 2015[ 8 ]; Topuz et al, 2014[ 39 ]; Turan, 2020[ 40 ]; Lai et al, 2012[ 19 ]; Ledda et al, 2021[ 21 ]; Iacobellis et al, 2008[ 15 ]; Meng et al, 2018[ 27 ]) and five case-control studies (Iacobellis et al, 2014[ 12 ], Colak et al, 2012[ 5 ], Yilmaz et al, 2011[ 43 ], Sunbul et al, 2014[ 37 ], Oğuz et al, 2016[ 30 ]), published between 2008 and 2021, which met our inclusion criteria were reviewed. Out of these, fourteen studies measured EAT thickness using echocardio-graphy; in the rest, EAT volume was assessed using CT or MRI methods (Brouha et al, 2018[ 3 ]; Granér et al, 2015[ 8 ]; Ledda et al, 2021[ 21 ]; Meng et al, 2018[ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 58 articles were excluded because they did not meet the inclusion criteria. Finally, 18 articles (thirteen cross-sectional studies (Fracanzani et al, 2016[ 7 ]; Brouha et al, 2018[ 3 ]; Cho et al, 2017[ 4 ]; Kim et al, 2016[ 18 ]; Psychari et al, 2016[ 33 ]; Petta et al, 2015[ 32 ]; Granér et al, 2015[ 8 ]; Topuz et al, 2014[ 39 ]; Turan, 2020[ 40 ]; Lai et al, 2012[ 19 ]; Ledda et al, 2021[ 21 ]; Iacobellis et al, 2008[ 15 ]; Meng et al, 2018[ 27 ]) and five case-control studies (Iacobellis et al, 2014[ 12 ], Colak et al, 2012[ 5 ], Yilmaz et al, 2011[ 43 ], Sunbul et al, 2014[ 37 ], Oğuz et al, 2016[ 30 ]), published between 2008 and 2021, which met our inclusion criteria were reviewed. Out of these, fourteen studies measured EAT thickness using echocardio-graphy; in the rest, EAT volume was assessed using CT or MRI methods (Brouha et al, 2018[ 3 ]; Granér et al, 2015[ 8 ]; Ledda et al, 2021[ 21 ]; Meng et al, 2018[ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of studies are shown in the Table 1 (Tab. 1) (References in Table 1: Brouha et al, 2018[ 3 ]; Cho et al, 2017[ 4 ]; Colak et al, 2012[ 5 ]; Fracanzani et al, 2016[ 7 ]; Granér et al, 2014[ 8 ]; Iacobellis et al, 2008[ 15 ]; Iacobellis et al, 2014[ 12 ]; Kim et al, 2016[ 18 ]; Lai et al, 2012[ 19 ]; Ledda et al, 2021[ 21 ]; Meng et al, 2018[ 27 ]; Oğuz et al, 2016[ 30 ]; Petta et al, 2015[ 32 ]; Psychari et al, 2016[ 33 ]; Sunbul et al, 2014[ 37 ]; Topuz et al, 2014[ 39 ]; Turan, 2020[ 40 ]; Yilmaz et al, 2011[ 43 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have reported a relationship between EFTT and MS and cardiovascular risk factors. [ 26 , 27 ] Epicardial adipose tissue is metabolically active and secretes some adipokines and inflammatory cytokines. [ 28 , 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…130 Moreover, in a cohort of patients with metabolic syndrome, the severity of EAT and NAFLD was found to be highly correlated. 131,132 EAT is known as a source of proinflammatory cytokines (IL-1, IL-6, and TNF), which have an established role in the pathogenesis of atrial fibrillation and CV autonomic dysfunction (CVAD). [133][134][135] Unlike skeletal muscle where perimuscular fat is separated from myocytes through specific structures of connective tissue, within the heart, adipocytes are in close contact with both cardiomyocytes and nervous system and directly influencing their function.…”
Section: Cardiac Steatosismentioning
confidence: 99%